The role of organizational culture in moderating the relationship between ethical reasoning and auditors’ acceding to clients’ request / Abdolreza Shafiei - Abdolreza, Shafiei (2017)
Corporate governance (CG) entails legislation, provisions, structures, processes, cultures, and policies, leading to the realization of responsibility, transparency, justice, and observation of beneficiaries’ rights. Due to the importance of the auditor’s report and audit quality, the external auditor is assumed to be one of the most prominent components of this mechanism. Being ethical would prompt corporate governance to observe beneficiaries’ rights and protect them from possible dangers, such as auditor acceding. Acceding to the client’s request may jeopardize the auditor’s independence and endanger the mechanism of CG. Investigations in the field of ethical decision-making or ethical behavior in the auditing profession are expanded toward the analysis of factors that influence the ethical reasoning abilities of auditors. It helps demonstrate the necessity of reconsidering approaches that would help enhance the ethical judgment of individuals in audit firms. This study compares the auditors’ levels of ethical reasoning (as measured by P-scores) among members of the Iranian Association of Certified Public Accountants (IACPA) working in the private and public sectors. It also examines the possible relationship between the levels of ethical reasoning and the extent of auditor acceding for the two groups of auditors in Iran. The study explores the moderating role of the organizational culture in the relationship between ethical reasoning and auditors’ response to the client’s request (auditor acceding) within the same sample. Rest’s DIT-2 instrument was used to measure ethical reasoning, while Organizational Culture Profile (OCP) was used to measure organizational culture. A survey questionnaire method was adopted in this study involving a total of 432 auditors who are members of IACPA. The data were analyzed using SPSS software (v.20). An inverse relationship was reported between ethical reasoning and auditor acceding for the two groups of auditors, implying that higher levels of ethical reasoning will result in lower levels of acceding to a client’s request in a conflict scenario. The findings indicate that the Iranian auditors could remain independent by not acceding to the client’s request in a conflicting event. The results demonstrate that organizational culture moderates the relationship between ethical reasoning and auditor acceding. This study makes several contributions. It demonstrates that a higher level of auditors’ ethical reasoning reduces the auditor’s propensity to accede to the client’s request in an ethical dilemma scenario. It was found that the organizational values moderate the relationship between ethical reasoning and auditor acceding. The results contribute to enhancing the understanding of the role of organizational culture in the development of organizational values in auditing firms. Applying the ethical reasoning measurement (DIT-2) in adeveloping country context provides a new dimension in understanding the theory of moral reasoning since the majority of previous studies were carried out in developed countries.